Taking charge of your career - Woodward, Leanne; Bernstein, Amy; Abrams, Stacey; Hodgson, Lara; Cohen, Paige; Edwards, Laurie (HBR women at work series., 2023)
A purposeful career path starts with you. As a woman, navigating your career path can be challenging. At times you're faced with lack of support, unconscious bias and negative assumptions, disruptive career pauses, and more. So how can you get beyond these obstacles and progress your career in a way that is meaningful and fulfilling? Taking Charge of Your Career helps listeners navigate the tricky territory of charting a rewarding career path. Whether you're new to the workforce, reentering after a pause, or trying to find your way through a midcareer slump, you'll find research, advice, and practical tips to help you move forward. This book will inspire you to: decide what a meaningful career looks like to you, align yourself with the right supporters and mentors, approach hard decisions with confidence, navigate difficult transitions, and be your own biggest advocate.